Toward the development of a conceptual framework for the complex interaction between environmental changes and rural-urban migration - Mianabadi, Ameneh; Davary, Kamran; Mianabadi, Hojjat; Kolahi, Mahdi; Mostert, Erik (Frontiers in Water, 2023)
Environmental change would result in dramatic increases in human migration as households became incapable of adapting to environmental change. Dealing with environmental migration is a complex issue that may turn into a wicked problem. Despite the growing literature on the nexus of environmental change and migration, issues of coupling and inextricable linkage between nature and society have made it difficult to establish causal relations between the two. To investigate the environment-migration nexus, it is necessary to develop a conceptual model that takes into account the causality of environmental changes as a cause of rural-urban migration (RUM). The prominence of the model is built on an enhanced understanding of the factors through which environmental-induced migration occurs. Such a model is developed in this paper, focusing on the decline of agricultural lands and products as well as the economic repercussions. The proposed model is based on the model of Perch-Nielsen et al. (2008) and incorporates additional factors that were not included in their model. RUM, in this paper, is driven by three main and leading causes, as primary push factors, including climate change, human maladaptive activities, and hydro-climatic disasters. A number of other factors are also incorporated into the model as additional causes (pull factors in cities) and counter-causes (governmental plans and individuals’ characteristics). The model contributes to bridging the knowledge gap regarding the effects of migration policymaking and environmental and climate change. Understanding the causality of interactions between environmental change and RUM will help broaden the range of possible policy responses for policymaking through sustainable management plans.